Evaluation of the rotational stiffness of precast reinforced concrete beam-column connections - Moreira, Gustavo (2024)
Publisher Copyright: © 2024 The Authors The authors would like to acknowledge the support of Concremat – Soluções de Betão, S.A. precast facility for fabricating the tested specimen